Analisis Sharia Compliance Pada Produk Kafalah Pembiayaan Surety Bond di PT.Penjaminan Jamkrindo Syariah Kantor Cabang Medan - Liana, Vega; Arif, Muhammad; Jannah, Nurul (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This research is the result of a qualitative descriptive study that aims to answer questions regarding the mechanism for the issuance of Kafalah products for Surety Bond Financing and Sharia Compliance for Kafalah Surety Bond Financing products at PT Penjaminan Jamkrindo Syariah Medan Branch Office. This research is a type of field research. Data collection was carried out through direct interviews with Surety Bond staff and other operational divisions at PT. Medan Sharia Jamkrindo Guarantee. Supported by the study of documents related to research, such as statutory regulations, DSN-MUI Fatwas, and Kafalah surety bond certificates and official websites. Then the results collected were analyzed in the form of a qualitative descriptive analysis method. The results of the research obtained are the first, regarding the mechanism of the process of issuing Kafalah products for Surety Bond Financing from three parties, namely the Project Owner (Obligee) then continued by the Contractor (Principal), namely the party that gives the achievement and finally we submit it to the Guarantee (Suretyship) /Surety Company) to process Company guarantees to be given or claimed to the principal and submitted to the obligee. secondly, namely in carrying out the guarantee business activities of PT. The Jamkrindo Syariah Guarantee uses the Kafalah contract as determined by the National Sharia Council, namely DSN-MUI FATWA No.11/DSN-MUI/IV/2000 concerning Kafalah, including its application in Kafalah Surety Bond Financing products. However, there are still a number of things that need to be emphasized again, one of the pillars and conditions of Makful Anhu, namely being known by the guarantor and being able to hand over his dependents to the guarantor. So here a Surety bond is a guarantee issued by an insurance company to help the obligee due to the failure of the principal to carry out the project (default). So surety bonds are an alternative form issued by loss insurance companies (Guarantee) and PT. The Jamkrindo Syariah guarantee is expected to be able to maintain adherence to Sharia Compliance, which is currently well fulfilled.